Profitabilitas, Likuiditas, Pertumbuhan Penjualan, dan Ukuran Perusahaan Terhadap Kebijakan Utang pada Perusahaan Sub Sektor Makanan dan Minuman - Sri Agustini; Sugeng Iscahyono; Abdul Yogi Puadudin (Journal of Academia Perspectives, 2022)
This study aims to determine and analyze the effect of Profitability, Liquidity, Sales Growth, and Company Size on Debt Policy. For this reason, every company that has a goal to get maximum profit requires large capital, one of the sources is from external funds in the form of funds that obtained from other parties or debts. The research method used in this research is associative research method, namely research that aims to determine the influence or relationship between two or more variables. The results of the study show that for food and beverage companies listed on the Indonesia Stock Exchange in 2016-2018 that profitability has no effect on debt policy, as evidenced by the profitability significance value of 0.336 which is greater than the significance value of 0.05. Liquidity has an effect on debt policy, as evidenced by the significance value of 0.023 which is smaller than the value of 0.05. Then, sales growth has no effect on debt policy, as evidenced by a significance value of 0.283 greater than 0.05. And, firm size has no effect on debt policy, as evidenced by a significance value of 0.411 which is greater than 0.05. Partially shows that three variables, namely profitability, sales growth and firm size have no effect on debt policy, and one variable, namely liquidity, which affects debt policy. The results of the research simultaneously show that profitability, liquidity, sales growth and firm size together have no effect on debt policy. And the results simultaneously show that 0.039 is smaller than 0.05 simultaneously profitability, liquidity, sales growth and firm size affect debt policy.